Larval chondrocranium morphology of five species of Proceratophrys Miranda-Ribeiro (Amphibia; Anura; Odontophrynidae) - Dias, Pedro Henrique Dos Santos; de Carvalho-E-Silva, Ana Maria Paulino Telles; de Carvalho-E-Silva, Sergio Potsch (Zootaxa, 2013)
The chondrocranium and hyobranchial morphology are described for the tadpoles of five species of Proceratophrys Miranda-Ribeiro. The chondrocranium of P. appendiculata, P. boiei, P. laticeps and P. tupinamba are very similar and can be distinguished from that of P. cristiceps by: 1) less developed processus muscularis; 2) thinner palatoquadrate; 3) broad-est ethmoidal region; 4) longer cornua trabeculae; and 5) morphology f the suprarostral cartilages. A morphological vari-ation among Proceratophrys boiei is described. It reveals the existence of at least three distinct evolutionary lineages under this name. A brief comparison with other cycloramphid species is also provided.